Classical spin simulations with a quantum two-spin correction - Navez, Patrick; Starkov, Grigory A.; Fine, Boris V. (Arxiv, 2018)
Classical simulations of high-temperature nuclear spin dynamics in solids are known to accurately predict relaxation for spin 1/2 lattices with a large number of interacting neighbors. Once the number of interacting neighbors becomes four or smaller, classical simulations lead to noticeable discrepancies. Here we attempt to improve the performance of the classical simulations by adding a term representing two-spin quantum correlations. The method is tested for a spin-1/2 chain. It exhibits good performance at shorter times, but, at longer times, it is hampered by a singular behavior of the resulting equations of motion.
Gesehen am 19.11.2020